Supporting data for the manuscript "Ice nucleating particle emissions from photochemically-aged diesel and biodiesel exhaust" - Schill, Gregory P.; Jathar, Shantanu; Kodros, John K.; Levin, Ezra J. T.; Galang, Abril M.; Friedman, Beth; Link, Michael F.; Farmer, Delphine K.; Pierce, Jeffrey R.; Kreidenweis, Sonia M.; DeMott, Paul J. (Colorado State University. Libraries, 2016)
Immersion-mode ice-nucleating particle concentrations from an off-road diesel engine were measured with a Continuous Flow Diffusion Chamber (CFDC). Both petrodiesel and biodiesel were used, and the exhaust was aged up to 1.5 photochemically equivalent days. Total aerosol and refractory black carbon concentrations were determined in this study with a Scanning Mobility Particle Sizer (SMPS) and Single Particle Soot Photometer, respectively. The CFDC, SMPS, and SP2 data used in this study can be found in this archive.
Department of Atmospheric Science